Urban climate adaptation as a process of organisational decision making - Taylor, Anna (Department of Environmental and Geographical Science, 2018)
In a world that is increasingly urbanised, cities are recognised as critical sites for tackling problems of climate change, both by reducing greenhouse gas emissions and addressing the impacts of changing climate conditions. Unlike climate change mitigation, adaptation does not have one clear, commonly agreed collective goal. Governing and making decisions on climate adaptation in cities entails contestation over knowledge, values and preferences. Currently, the two dominant conceptualisations of adaptation are as cycles or pathways. Do these models adequately theorise what can be empirically observed in cities as to how climate adaptation is undertaken? Most research on urban climate adaptation emanates from the Global North, where political, scientific, economic and administrative systems are well established and well resourced. There is a dearth of empirical research from cities of the Global South contributing to the development of urban climate adaptation theory. This thesis contributes to addressing this gap in two ways. Firstly, by drawing on both conceptual and methodological resources from the field of organisational studies, notably the streams and rounds models of decision making, organisational ethnography and processual case research. Secondly, by conducting empirical case study research on three processes of city scale climate adaptation in Cape Town, South Africa, a growing city facing many development challenges where the local government began addressing climate adaptation over ten years ago. The three adaptation processes studied are: the preparation and adoption of city-wide sectoral climate adaptation plans; the creation of a City Development Strategy with climate resilience as a core goal; and the inclusion of climate change projections into stormwater masterplans. Data were gathered through interviews, participant observation, focus groups and document review, through embedded research within a formal knowledge co-production partnership between the University of Cape Town and the City of Cape Town government. Processual analysis and applied thematic analysis were used to test models of adaptation and decision making against data from the three case studies. The findings suggest that both the cycles and pathways models of climate adaptation inadequately represent the contested and contingent nature of decision making that prevail within the governance systems of cities such as Cape Town. Based on ethnographic knowledge of how Cape Town's local government undertakes climate adaptation, it is argued that the rounds model of decision making provides conceptual tools to better understand and represent how the process of climate adaptation in cities is undertaken; tools that can be used to enhance the pathways model. The study concludes that progress in adapting cities to a changing climate is currently constrained by both the problems and potential solutions or interventions being too technical for most politicians to deal with and prioritize and too political for most technical and administrative officials to design and implement. It calls for urban climate adaptation to be understood as distributed across a multitude of actors pursuing concurrent, discontinuous processes, and thereby focus needs to be on fostering collaboration and coordination, rather than fixating on single actors, policies, plans or projects.